Prolong placement of tracheostomy tube causing unusual complication - Mohamad Norkahfi R,; Marina Mat Baki,; Mawaddah Azman,; Abdullah Sani Mohamed, (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2016)
Tracheostomy can be associated with numerous complications. Here, we present a case of large hypertrophic skin of tracheostoma with tracheal granulation tissue causing malpositioning of tracheostomy tube and airway obstruction, secondary to prolong placement of a cuff tracheostomy tube due to improper tracheostomy care. This case illustrates that awareness and knowledge of proper tracheostomy tube care among medical personnel are very important to avoid any mismanagement that can cause life-threatening complications.